Genetic incorporation of d-amino acids into green fluorescent protein based on polysubstrate specificity1. Issue 49 (30th May 2015) - Ma, Hairong; Liu, Nan; Shi, Shaobo; Wang, Shuzhen; Chen, Yijun
<x xml:space="preserve">Abstract</x> A number of d-amino acids were genetically incorporated into green fluorescent protein, and the GFPuv mutant containing d-phenylalanine in the fluorophore at residue 66 was characterized.